2009
DOI: 10.1007/s12284-009-9034-y
|View full text |Cite
|
Sign up to set email alerts
|

Australian Oryza: Utility and Conservation

Abstract: Australian Oryza are an understudied and underexploited genetic resource for rice improvement. Four species are indigenous: Oryza rufipogon, Oryza meridionalis, Oryza australiensis are widespread across northern Australia, whereas Oryza officinalis is known from two localities only. Molecular analysis of these wild populations is required to better define the distinctness of the taxa and the extent of any gene flow between them and rice. Limited collections of these wild populations are held in seed and DNA ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 27 publications
0
80
0
Order By: Relevance
“…This diversity in the genus is an important resource, which is being studied to improve rice yield, especially under unfavorable environmental conditions. In particular, O. glaberrima, Oryza australiensis, and Oryza meridionalis are of interest as drought-tolerant species (Henry et al, 2010;Ndjiondjop et al, 2010;Scafaro et al, 2011Scafaro et al, , 2012, while Oryza coarctata is salt tolerant (Sengupta and Majumder, 2010). In this study, a total of 43 leaf functional and structural parameters were collected on 24 accessions corresponding to 17 species within eight genomes (Table I) to represent the spectrum of the leaf diversity in the genus Oryza.…”
mentioning
confidence: 99%
“…This diversity in the genus is an important resource, which is being studied to improve rice yield, especially under unfavorable environmental conditions. In particular, O. glaberrima, Oryza australiensis, and Oryza meridionalis are of interest as drought-tolerant species (Henry et al, 2010;Ndjiondjop et al, 2010;Scafaro et al, 2011Scafaro et al, , 2012, while Oryza coarctata is salt tolerant (Sengupta and Majumder, 2010). In this study, a total of 43 leaf functional and structural parameters were collected on 24 accessions corresponding to 17 species within eight genomes (Table I) to represent the spectrum of the leaf diversity in the genus Oryza.…”
mentioning
confidence: 99%
“…Australia is a center of diversity and the possible origin of the AA genome group (Brozynska et al, 2017). There is considerable scientific interest in the wild species because of their potential to be used in rice breeding programs (Henry et al, 2010) but also because of the risks they pose to rice production by acting as reservoirs of pests and pathogens (Khemmuk et al, 2016;Petrovic et al, 2013). The fungus Pyricularia oryzae, the cause of blast disease, is thought to have jumped from wild to domesticated rice in north Queensland, an event that has led to the temporary abandonment of cropping in parts of Cape York Peninsula until disease management strategies can be devised (Khemmuk et al, 2016).…”
mentioning
confidence: 99%
“…Taxon A and Oryza sp. Taxon B), grow on flood plains and the fringes of lagoons, and are perennial, dying back to buried rhizomes during the dry season (Henry et al, 2010). Many perennial monocots, such as sugarcane and banana, support large assemblages of plant viruses, probably due to the fact that infections persist from one generation to the next via vegetative propagation of the plants e.g.…”
mentioning
confidence: 99%
“…Although it might be argued that these reported new taxa are hybrid swarms originating from crosses between O. sativa and Australian wild rice, these authors have discounted this, based on molecular data. O. rufipogon was initially thought to occur in both Asia and Australia (Henry et al 2009;Vaughan 1994), with ecological and geographical isolation causing the observed genetic differentiation. However, some scientists believe that this may have been inaccurate and suggest the germplasm originally christened as O. rufipogon from Australia in fact represents the two newly identified taxa (Brozynska et al 2014).…”
Section: Relationship Between O Rufipogon O Sativa and O Nivaramentioning
confidence: 99%
“…While information on the utilization and conservation of other wild species have been reviewed (e.g. Henry et al 2009;Song et al 2005), no such efforts have been made for the African Oryza species. This chapter provides an overview of the status of conservation and utilization of African Oryza species and identifies gaps in knowledge and opportunities for further research.…”
Section: Introductionmentioning
confidence: 99%